Star formation in the Dwarf Seyfert Galaxy NGC 4395: evidence for both AGN and SN feedback? - Nandi, Payel; Stalin, C. S.; Saikia, D. J.; Muneer, S.; Mountrichas, George; Wylezalek, Dominika; Sagar, R.; Kissler-Patig, Markus (The astrophysical journal, 2023)
We present a detailed multiwavelength study of star formation in the dwarf galaxy NGC 4395, which hosts an active galactic nucleus (AGN). From our observations with the Ultra-Violet Imaging Telescope, we have compiled a catalog of 284 star-forming (SF) regions, out of which we could detect 120 SF regions in Hα observations. Across the entire galaxy, we found the extinction-corrected star formation rate (SFR) in the far ultraviolet (UV) to range from 2.0 × 10−5 M ⊙ yr−1 to 1.5 × 10−2 M ⊙ yr−1 with a median of 3.0 × 10−4 M ⊙ yr−1, and the age to lie in the range of ∼1 to 98 Myr with a median of 14 Myr. In Hα we found the SFR to range from 7.2 × 10−6 M ⊙ yr−1 to 2.7 × 10−2 M ⊙ yr−1 with a median of 1.7 × 10−4 M ⊙ yr−1, and the age to lie between 3 to 6 Myr with a median of 5 Myr. The stellar ages derived from Hα show a gradual decline with galactocentric distance. We found three SF regions close to the center of NGC 4395 with high SFRs both from Hα and UV, which could be attributed to feedback effects from the AGN. We also found six other SF regions in one of the spiral arms having higher SFRs. These are very close to supernova remnants, which could have enhanced the SFR locally. We obtained a specific SFR (SFR per unit mass) for the whole galaxy of 4.64 × 10−10 yr−1.